Caring for children – '24-7': The experience of WellChild Nurses and the families for whom they are providing care and support. (March 2019) - Whiting, Mark
There is a growing population of children with complex health needs and disabilities who are being cared for at home by their parents 24 hours per day, 7 days per week. Community Children's Nursing Teams are a major source of support to these children. In 2006, the charity WellChild introduced the first WellChild Nurse (WCN) post specifically focused upon this group of children. In order to gain insight into how the WCN model was supporting this group of children throughout the 24-hour day, semi-structured interviews were undertaken with 12 WCNs and 10 parents of children with a range of long-term clinical care needs. Analysis of the interviews from both groups of study participants revealed complex patterns of decision-making by parents when seeking support and advice particularly 'out of hours'. This related to four key questions: 'Why call?', 'When to call?', 'Who to call?' and 'How to call?'. Parents identified how, as a result of the support provided by the WCNs, they are able to draw upon a range of decision-making skills and algorithms that enhance their ability to troubleshoot both clinical and non-clinical problems throughout the 24-hour day.